ANALISIS PENGALAMAN KERJA, KOMPETENSI, PENDIDIKAN DAN PELATIHAN TERHADAP PENGEMBANGAN KARIR DENGAN INTERVENING PRESTASI KERJA - Pangestuti, Dewi Cahyani (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to identify factors that influence of job performance and career development at the Rehabilitation Center of the Ministry of Defence. Data were collected from 65 respondents using self-administration questionnaires, and path analysis was used to test the hypotheses. The results show that work experience, competencies, and training directly affect performance, but only work experiences that directly affect career development. Finally, performance directly affects employee career development. Implications and suggestions are explained in the paper.